PENINGKATAN KETERAMPILAN MEMBACA NYARING DENGAN MENGGUNAKAN MODEL PEMBELAJARAN FONETIK DI SEKOLAH DASAR - alsabila, Khairunnisa; Marta, Rusdial; Fadhilaturrahmi; Hana Pebriana, Putri; Nurhaswinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low results of improving students' reading aloud skills in Indonesian language lessons in grade 3 of UPT SD Negeri 014 kumantan. One solution to overcome this problem is to apply a phonetic learning model. The purpose of this study is to improve students' reading aloud skills in Indonesian language lessons. The learning model of this research is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and 4 stages: planning, implementation, observation and reflection. The time of the research was carried out in July 2025. The subjects of this study were 15 third grade students, or 6 boys and 9 girls. Data collection techniques were observation and documentation. The results of the study showed that using a phonetic learning model can improve students' reading aloud skills. This was shown before the research, students' reading aloud skills were 66.6%, then in cycle I meeting I still remained 66.6%, Cycle I meeting II increased to 73.3%. Furthermore, in Cycle II, meeting I, it increased to 80% and in Cycle II, meeting II, it increased to 93.3%. Thus, it can be concluded that using the phonetic learning model can improve students' reading aloud skills in Indonesian language learning at the UPT SD Negeri 014 Kumantan.